Literature Study: Principal's Managerial Policy and Teacher Performance on School Achievement - Setianingsih, Dewi Mindar; Roesminingsih, Erny; Trihantoyo, Syunu; Hazin, Mufarrihul; purwoko, Budi (Publik : (Jurnal Ilmu Administrasi), 2025)
A number of organizational techniques are utilized in curriculum preparation with the goal of maximizing student comprehension.  In order to demonstrate that the specified curriculum is being implemented, educators must make sure that curriculum planning satisfies students' educational needs and that students acquire new knowledge, attitudes, and abilities that improve their learning behavior. The study uses a qualitative descriptive method and uses a Systematic Literature Review (SLR) approach which aims to describe the findings of researchers on several journal articles found. The types of data sources or objects of study used in this study are scientific articles on the managerial abilities of school principals from national and international journals published from 2020 to 2024. With the process of collecting article data in the Google Scholar database. Based on the results, it can be seen that the principal as a manager has an important role in optimizing school functions. Principal managerial includes a series of activities that include:  (1) planning, (2) organizing, (3) directing/leading, (4) controlling, (5) evaluating and developing. Principal managerial policies have a positive and significant effect on teacher performance and also have a positive effect on school achievement. It is certainly based on some of these studies, it is recommended that school principals really master the managerial abilities of school principals so that the desired goals can be achieved properly and maximally.